The Role of Corporate Risk as a Moderating Variable: The Effect of Transfer Pricing and Capital Intensity on Tax Aggressiveness - Sinta Puji Lestari; Ahmad Yani; Dewi Wungkus Antasari (Jurnal Riset Perpajakan: Amnesty, 2026)
Tax aggressiveness remains a major challenge in the mining industry due to the complexity of related-party transactions, substantial fixed-asset investments, and opportunities for profit shifting. This study investigates the effects of transfer pricing and capital intensity on tax aggressiveness while examining the moderating role of corporate risk. Grounded in Agency Theory, the study argues that managerial incentives and risk preferences shape corporate tax planning decisions. A quantitative research design was employed using secondary data from audited annual reports of mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Purposive sampling produced 50 firm-year observations. The hypotheses were tested using Multiple Linear Regression and Moderated Regression Analysis (MRA). The results indicate that transfer pricing has a significant positive effect on tax aggressiveness, suggesting that related-party transactions increase opportunities for tax minimization. Conversely, capital intensity has a significant negative effect, indicating that firms with greater fixed-asset investments tend to adopt more conservative tax strategies because depreciation policies are more transparent and tightly regulated. Furthermore, corporate risk strengthens the positive relationship between transfer pricing and tax aggressiveness but weakens the relationship between capital intensity and tax aggressiveness. The study contributes to the tax compliance and Agency Theory literature by demonstrating that corporate risk functions as a contingency factor influencing the effectiveness of tax planning strategies. The findings also provide practical implications for tax authorities in strengthening risk-based supervision of transfer pricing and improving tax compliance within the mining sector.